Evaluating the Influence of Sample Size and Taxonomic Group on Chao s Estimator of Species Richness Using iNaturalist Photographic Observations in Honduras - Alvarado V., Fernanda L. (Zamorano: Escuela Agrícola Panamericana, 2025)
Species richness estimation is an important tool for biodiversity assessment and conservation. However, numerous factors can affect the accuracy of these estimates, such as sample size and the taxonomic group studied. This study evaluated the applicability of Chao's species richness estimator in different taxonomic contexts using photographic observations from the iNaturalist platform in Honduras. Counts of low abundance individuals (observed 1 or 2 times) were conducted, and data from reptiles, birds, bats, and amphibians were analyzed based on photographic observations from the iNaturalist citizen science platform. Species presence was monitored in different sampling areas, varying in size and sampling effort. Additionally, the effectiveness of Chao's estimator was compared in these areas to determine its reliability at different sample sizes. The results highlight the importance of adequate sampling effort to obtain accurate estimates, especially for underrepresented taxa. This study provides a baseline for future research to improve biodiversity estimation methods from incomplete inventories and their application in conservation strategies.